Prarancangan Pabrik Fenol Formaldehida Dengan Katalis Asam (Resin Novolak) Kapasitas 20.000 Ton/Tahun - Nurdiansah, Taofik, Ir. Haryanto.A.R, M.S, Emi Erawati, S.T, M.Eng (2016)
Novolac resin is one kind of phenol formaldehyde resins in the manufacture using an acid catalyst. Novolac resins has several uses, among others, are used as lacquers, laminating materials, wood adhesives, varnishes and is also used in wall decoration panel. Needs novolak resin itself in Indonesia is still quite high, from 2009 to 2014 every year has increased. Novolak resin plant capacity is 20,000 tons/year, all operating for 330 days, the raw material phenol and formaldehyde, with the ratio 1: 0.8 and the use of sulfuric acid catalyst. Novolac resin forming reaction is an exothermic reaction that occurs in the reactor CSTR, liquid-liquid phase, irreversible with the reaction conditions are maintained at a temperature of 95°C (isothermal) and a pressure of 1 atm. Novolac resin plant with a capacity of 20,000 tons /year of phenol requires raw materials as much as 1955.235 kg/hour, formaldehyde as much as 1660.630 kg /h and sulfuric acid catalyst as much as 138.547 kg/hour. Novolac resin plant requires much water as 28353.631 kg / h obtained from the river. Saturated steam needs as much as 3535.578 kg/h obtained from the boiler with diesel fuel as much as 0.318 m3/hour. While electricity obtained from the PLN and a capacity of 3500 KW generator as a backup, with as much fuel as 344.139 kg/hour. Compressed air needs as much as 56.074 m3/h. The factory is planned to be established in an industrial area Gresik, East Java, with a land area of 15,000 m2 and the number of employees 163 people. From the analysis of the economic, novolac resin plant requires capital of US $ 31,295,996.43 fixed and working capital of US $ 8,783,730.13. Profit before tax of US $ 11,297,654.14/year. While profit after tax of US $ 9,038,123.31/year. The feasibility analysis is a result that Percent Return On Investment (ROI) before tax of 36.0994% and after tax of 28.8795%. Pay Out Time (POT) before tax was 2.17 years, while after tax of 2.57 years. Break Even Point (BEP) of 46.2429% capacity, and Shut Down Point (SDP) of 26.8840% capacity. Discounted Cash Flow (DCF) of 47.4098%. Based on the data above, the novolac resin plant is quite interesting to be established. Keywords: phenol, formaldehyde, sulfuric acid